The contribution of Quality Management to Risk Management: Application of Quality Tools - Safia Benmehdi (Advanced Research in Economics and Business Strategy Journal)
It is very common to describe quality as customer satisfaction, its management is developing more and more, we are trying in this research paper some of its tools for risk management, and the latter is part of a movement that ensures the security and continuity of any project. Our objective is to respond to the main issue, which revolves around the advantages of quality management for better risk management through its tools, the FMEA method, the Pareto diagram, and the ISHIKAWA diagram. To achieve this, we offer a qualitative approach based on content analysis. Of which a public works company project constitutes the element of our study. In order to manage and assess the risks associated with this project, the results of our study will be defined throughout this research work.